The experience of patients with lymphoedema undergoing a period of compression bandaging in the UK and Canada using the 3M™ Coban™ 2 compression system - Morgan, Philip A (Int Wound J, 2011)
This article reports on a qualitative study that explored the experience of patients who have undergone a period of complete decongestive therapy using the 3M™ Coban™ 2 compression system (Coban 2 system). Qualitative data were collected from 12 patients from the UK and 8 from Canada with a range of presentations of lymphoedema. Single semi‐structured interviews were used and participants were asked questions relating to their experience of diagnosis, the impact of lymphoedema on their lives, previous treatment using multilayer lymphoedema bandaging and their experiences of the 3M™ Coban™ 2 system. Treatment with multilayer lymphoedema bandaging was seen as constraining in that it was tiring, time consuming, heavy, bulky and led to feelings of clumsiness and a restricted life. Treatment with the 3M™ Coban™ 2 system was reported as enabling in that it was quicker and easier to apply, increased mobility, enhanced patient confidence and provided a sense of control and well‐being. The article also explores how aspects of the 3M™ Coban™ 2 system might be improved from the patient's point of view.